Variation in the composition of corals, fishes, sponges, echinoderms, ascidians, molluscs, foraminifera and macroalgae across a pronounced in-to-offshore environmental gradient in the Jakarta Bay–Thousand Islands coral reef complex. Issue 2 (30th September 2016) - Cleary, D.F.R.; Polónia, A.R.M.; Renema, W.; Hoeksema, B.W.; Rachello-Dolmen, P.G.; Moolenbeek, R.G.; Budiyanto, A.; Yahmantoro,; Tuti, Y.; Giyanto,; Draisma, S.G.A.; Prud'homme van Reine, W.F.; et al.
Abstract: Substrate cover, water quality parameters and assemblages of corals, fishes, sponges, echinoderms, ascidians, molluscs, benthic foraminifera and macroalgae were sampled across a pronounced environmental gradient in the Jakarta Bay–Thousand Islands reef complex. Inshore sites mainly consisted of sand, rubble and turf algae with elevated temperature, dissolved oxygen, pH and chlorophyll concentrations and depauperate assemblages of all taxa. Live coral cover was very low inshore and mainly consisted of sparse massive coral heads and a few encrusting species. Faunal assemblages were more speciose and compositionally distinct mid- and offshore compared to inshore. There were, however, small-scale differences among taxa. Certain midshore sites, for example, housed assemblages resembling those typical of the inshore environment but this differed depending on the taxon. Substrate, water quality and spatial variables together explained from 31% (molluscs) to 72% (foraminifera) of the variation in composition. In general, satellite-derived parameters outperformed locally measured parameters. Graphical abstract: Highlights: Goal: assess changes in composition of eight taxa across an in-to-offshore gradient Relate changes in composition to cross-shelf variation in substrate and water quality Cross-shelf variation in taxon composition was globally similar. There were, however, small-scale differences among taxa. Inshore sites had depauperate assemblages and very low live coral cover.